96P Clearance of HPV anal premalignant lesions and modulation of systemic immune responses to HPV oncogenes with low dose pomalidomide. (15th December 2019) - Polizzotto, M; Van Bockel, D; Law, C; Roberts, J; Buckland, G; Just, S; Comben, S; Hillman, R; Gilson, R; Pett, S; Poynten, M; Law, M; et al.
Abstract: Background: Anal high-grade intraepithelial lesions (HSIL) precede the development of HPV-associated anal cancer and so present a target for early intervention and cancer prevention. Spontaneous HSIL clearance is associated with systemic CD4 T-cell response to the HPV oncogene E6. Pomalidomide may enhance immune responses to HPV and be therapeutic in HSIL. Methods: This phase II single centre study (NCT3113942) recruited participants with persistent (>12 months) biopsy-proven anal HSIL. Therapy was oral pomalidomide, 2mg for 21 of 28 days for up to 6 months. Primary outcome was response at end therapy (CR defined as histological clearance; PR as ≥ 50% reduction in area); secondary included response after 6 further months observation. Immune activation markers (CD38, HLA DR) were assessed with flow cytometry and antigen-specific CD4+ T-cell responses to HPV E6 and E7 with OX40 immunoassay. Results: 26 participants were enrolled, 24 were evaluable for response. All male; median age 54 (range 41-74). All AIN3 HSIL, median duration HSIL 37 months (15-86), median octants 2 (0.5-5); HPV16 in 55%; multiple high risk HPV types in 50%. Overall response (CR+PR) was 52% (CI: 31-73) at end therapy, increasing to 63% (95% CI 40-81) after 6 further months observation. Adverse events (AEs) were mild and self-limited, including cytopenias, constipation, and rash. Over 137 cycles (c), attributable grade 3/4 events were grade 3 neutropenia (4 c) and grade 3 angina (1 c). Systemic CD4 T-cell responses to HPV E6 but not E7 increased significantly during therapy, peaking day 14 of therapy: baseline 0.06%, (IQR 0.01 – 0.12%), median increase day 14 0.13% (IQR: 0.02 – 0.26%), p = 0.001. Activation of CD4 and CD8 cells increased significantly during therapy. Parameters returned to baseline after therapy. Conclusion: Low dose oral pomalidomide was well tolerated and induced durable continuing clearance of anal HSIL of multiple genotypes in even in chronic extensive disease. Induction of HPV-specific CD4+ responses and immune activation support an immunological mechanism of action. Immunotherapy with pomalidomide is a promising approach to prevention of anal cancer and potentially other HPV cancers. Clinical trial identification: NCT3113942. Legal entity responsible for the study: Kirby Institute, University of New South Wales, Sydney, Australia. Funding: Cancer Institute of New South Wales. Disclosure: All authors have declared no conflicts of interest.